2021
DOI: 10.3389/fpsyg.2021.654139
|View full text |Cite
|
Sign up to set email alerts
|

An Ecological Perspective of Food Choice and Eating Autonomy Among Adolescents

Abstract: Adolescence is an important developmental period marked by a transition from primarily parental-controlled eating to self-directed and peer-influenced eating. During this period, adolescents gain autonomy over their individual food choices and eating behavior in general. While parent-feeding practices have been shown to influence eating behaviors in children, little is known about how these relationships track across adolescent development as autonomy expands. The purpose of this qualitative study was to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 42 publications
2
54
0
Order By: Relevance
“…The finding that food preferences is one of the main factors influencing pupils’ food choices is in line with several previous studies [ 39 , 40 , 42 , 58 ]. A US study on free school breakfast showed that unfulfilled food preferences was a barrier to participation, and the children accepted being hungry rather than eating the school breakfast if they did not like it [ 39 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The finding that food preferences is one of the main factors influencing pupils’ food choices is in line with several previous studies [ 39 , 40 , 42 , 58 ]. A US study on free school breakfast showed that unfulfilled food preferences was a barrier to participation, and the children accepted being hungry rather than eating the school breakfast if they did not like it [ 39 ].…”
Section: Discussionsupporting
confidence: 92%
“…A rapid evidence review about school food provision in high-income countries identified that many barriers to participation were explicitly related to the school environment and neighborhoods rather than the school meal programs, such as access to competitive foods [ 58 ]. As other studies have shown [ 42 , 67 ], going to the mall or fast-food restaurants is part of adolescents’ increasing autonomy. In addition, independently seeking out foods and controlling their own food choices were important issues [ 42 ] found related to adolescents’ eating autonomy.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Self-reported sleep can deviate considerably from sleep assessed through objective measures such as actigraphy [ 41 ], and between-person effects assessed in cross-sectional research do not necessarily translate to within-person effects in direction or magnitude [ 37 ]. It may be particularly important to examine associations between caffeine consumption and dimensions of sleep health given that adolescents begin to gain autonomy over their own sleep behaviors [ 42 ] and diet [ 43 ] versus childhood.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors influence the formulation of dietary behaviors and self-directed food choices among the youth [52]. The relatively higher diet quality of our adolescent population compared to reports from other children and adolescent populations may be attributed to home and school influences on their dietary choices and behaviors.…”
Section: Discussionmentioning
confidence: 88%